Pharmacognostical and physiochemical evaluation of bruhaniya gana siddha ksheerpak for ksheerpan and ksheerbasti in the management of garbhashosh - Shinde, Sarika Trimbak (International Journal of Advances in Medicine, 2021)
Ayurveda is the most ancient medical science framed on evidence-based principles. So, the standardization of Ayurveda drugs is much needed work in view to asses and maintain the quality of Ayurveda drugs in present era. The WHO appreciated the importance of medicinal plants for public health care in developing nations and has evolved guidelines to support the member states in their efforts to formulate national policies on traditional medicine and to study their potential usefulness including evaluation, safety and efficacy. The quality assessment of Ayurveda drug formulations is very important in order to prove their acceptability in modern system of medicine. The present study aims to standardize bruhaniya gana siddha ksheerpaka formulation for ksheerpan and ksheerbasti in the management of garbhashosh (IUGR). The process of standardization is achieved by systematic pharmacognostical and physiochemical evaluative studies. The drug formulation bruhaniya gana siddha ksheer contains Bala, Ashwagandha, Shatawari, Vidari, Kakoli, and Kshirkakoli.2 Organoleptic characters revelled that formulation was light off white in colour, characteristic fragrant odour, and sweet in taste. The result of pharmacognostical study had shown presence of prismatic crystals of Bala, Scalariform vessels of Shatavari, and trichomes of Ashwagandha, cambial activity of the tubers of Vidari, etc. Physiochemical study showed loss on drying 2.96%, total ash 0.31%, acid insoluble ash 0.01%, pH 6.18%, total solids 34.68. Phyto-chemical analysis showed presence of alkaloids, tannins, steroids, proteins, carbohydrates, reducing sugar, etc. The formulation was prepared and screened for various standardization parameters as per ayurveda drug standard protocols in API.